Examining "Mass Probation" Through an Intersectional Lens: The Intracategorical Effects of Race and Ethnicity on Women and Men’s Probation Outcomes in Kansas - Boppre, Breanna (Crime & delinquency, 2024)
Community supervision increased dramatically since the early 2000s. Similar to trends in prison admissions, the increase has not been equal across racial and ethnic groups. In addition to disparities in placement onto supervision, experiences under supervision and outcomes may also be shaped by intersecting identities. Accordingly, this study examined probation outcomes among 4,433 probation cases in 2018 in Kansas. We assess how race and ethnicity impact outcomes among women and men while controlling for criminogenic risk and need, offense, financial stability, and other factors using multilevel modeling. Results indicate that race and ethnicity were unrelated to probation outcomes for women; however, Black men were subject to the worst odds of probation outcomes. Policy and future research implications are discussed.